O uso da interdiscinaridade no ensino de química sob o olhar da educação jesuítica - Maia, Ana Maria Ribeiro (Universidade do Vale do Rio dos Sinos, 2018)
The current Brazilian education legislation establishes that teaching should take place in a contextualized and interdisciplinary or transdisciplinary way aiming at the education of the student towards socializing and preparation for work. With the objective of presenting a teaching proposal that meets these assumptions, this work presents a meaningful approach to learning through a generative theme, supported by Ignatian pedagogy. The project was carried out at a basic education school in the municipality of Fortaleza, Santo Inácio College, part of the Jesuit Education Network. Through current data released by the World Health Organization (WHO) and observing the main problems of society the theme: Alcohol is not in me: say NO to Alcohol, it was proposed as a way to work the alcoholism and adolescence strand in an interdisciplinary and problematizing with the curricular components of Chemistry, Physics and Biology. In the methodological course the subjects were discussed: chemical and physical characteristics of the substances, effects of alcohol on the body, alcohol content, protein denaturation, oxidation, nomenclature of Organic Chemistry, nervous system balance. For evaluation, experimental activities and two theoretical evaluations of acquired knowledge were considered. The results show the main skills and abilities developed by the students during the application of the project in the disciplines contemplated. It is concluded that there is a greater interest in students' learning motivated by meaningful learning through a theme contextualized with their reality, providing a critical, innovative and conscientious education with the application of formal contents of the disciplines.
Keywords: Aprendizagem significativa; Tema gerador; Interdisciplinaridade; Pedagogia inaciana; Meaningful learning; Generator theme; Interdisciplinarity; Ignatian pedagogy